2022
DOI: 10.1186/s12871-022-01690-w
|View full text |Cite
|
Sign up to set email alerts
|

Delirium risk factors in hospitalized patient: a comprehensive evaluation of underlying diseases and medications in different wards of a large Urban Hospital Center in Iran

Abstract: Background Delirium is a neurobehavioral syndrome, which is characterized by a fluctuation of mental status, disorientation, confusion and inappropriate behavior, and it is prevalent among hospitalized patients. Recognizing modifiable risk factors of delirium is the key point for improving our preventive strategies and restraining its devastating consequences. This study aimed to identify and investigate various factors predisposing hospitalized patients to develop delirium, focusing mostly on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…This therapeutic class reduces excessive dopaminergic activity, a major contributing factor in delirium, which favors its prescription in critical care situations. 39 , 40 Studies have shown that delirium affects a significant proportion of older people in ICUs and that haloperidol, the predominant antipsychotic in the study sample, prevents delirium. 39 , 40 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This therapeutic class reduces excessive dopaminergic activity, a major contributing factor in delirium, which favors its prescription in critical care situations. 39 , 40 Studies have shown that delirium affects a significant proportion of older people in ICUs and that haloperidol, the predominant antipsychotic in the study sample, prevents delirium. 39 , 40 …”
Section: Discussionmentioning
confidence: 96%
“… 39 , 40 Studies have shown that delirium affects a significant proportion of older people in ICUs and that haloperidol, the predominant antipsychotic in the study sample, prevents delirium. 39 , 40 …”
Section: Discussionmentioning
confidence: 96%
“…The common characteristic is that they are quick screening scales, generally requiring less than 3 min, suitable to be performed in the ED ( 15 ). Early detection and intervention in people with delirium is a strong indicator of the quality of hospital care for vulnerable patients ( 16 , 17 ). Thus, this study aims to assess the accuracy of the 4AT scale, as administered by ED nurses in triage, and to compare time spent in triage between participants screened with the 4AT and those not screened.…”
Section: Introductionmentioning
confidence: 99%